Inter-visit measurement variability of conjunctival vasculature and circulation in habitual contact lens wearers and non-lens wearers - Wang, Jianhua (Eye Vis (Lond), 2019)
BACKGROUND: The inter-visit variation of measuring bulbar conjunctival microvasculature and microcirculation needs to be considered when the results from multiple visits are interpreted. This study examined the inter-visit variability of measuring conjunctival microvasculature and microcirculation in habitual contact lens (HCL) wearers and non-contact lens (NCL) wearers. METHODS: Twenty-eight subjects were recruited including 13 HCL wearers (10 females and 3 males; mean age ± standard deviation, 25.8 ± 4.6 years) who had worn contact lenses on a daily basis for at least 3 years and 15 NCL wearers (10 females and 5 males, age 25.5 ± 4.0 years) were recruited. The temporal bulbar conjunctiva was imaged using a functional slit-lamp bio-microscope (FSLB) imaging system. FSLB imaging was performed in the morning when the HCL wearers did not wear their lenses. The measurements included conjunctival vessel diameter, vessel density, blood flow velocity and flow volume. In addition, conjunctival microvasculature was analyzed using monofractal (Dbox, representing vessel density) and multifractal (D0 representing vessel complexity) analyses. The repeated measurement was conducted at least one week after the first visit and both eyes of each participant were imaged. The coefficient of variation (CV) was calculated as the standard deviation of the differences between test and re-test then divided by the mean of the measurements. The intra-class correlation coefficient (ICC) was also calculated. RESULTS: No significant differences of all vascular measurements in both the right and left eyes were found between two groups (P > 0.05). Between two measurements on two different visits, the CV was from 2.4% (vessel density D0) to 63.5% (blood flow volume Q) in HCL wearers and from 3.4% (D0) to 40.6% (blood flow volume) in NCL wearers. The ICC was from 0.60 (vessel diameter) to 0.81 (axial blood flow velocity VA) in HCL wearers and from 0.44 (Q) to 0.68 (cross-sectional blood flow velocity VS) in NCL wearers. CONCLUSIONS: The measurement variability of the vessel density of the bulbar conjunctiva appeared to have the smallest inter-visit variation. The measurement variability of the vasculature and circulation in HCL wearers were similar to that in NCL wearers.